Ethnomatematics Contain In Problem Based Learning to Improve Students Understanding about Geometry by Using Concept Of Cultural Buildings in Semarang (Universitas Negeri Semarang, 2018)
The purpose of this research was to analyze the model of Problem Based Learning based on ethnomatematics of cultural buildings in Semarang improving understanding of geometrical concepts of the fourth grade students’ of SD Negeri Candi 01 Semarang. The type of research was quantitative with true-experimental design by using pretest-posttest control design models. The subjects’ were 60 students of the fourth grade of elementary school that were divided proportially into a control group and an experimental group. The data collection technique used was essay test. The effectiveness was indicated from classical completeness with minimum completeness criteria (KKM), difference of average understanding of experimental and control class, improvement of understanding of geometry concept of experimental class. The results showed that (1) the understanding of the concept of geometry by using Problem Based Learning contained ethnomatematics of cultural building in Semarang has reached the classical completeness of 75%; (2) the average understanding about geometry concept of the experimental class with the learning model of Problem Based Learning contained ethnomatematics of cultural buildings in Semarang is better than the average understanding of the concept of geometry with the learning of Problem Based learning in the control group; (3) there is a difference in the understanding of the concept of geometry before and after the learning through Problem Based Learning contained ethnomatematics of cultural buildings in Semarang. In conclusion, the use of the Problem Based Learning contained ethnomatematics of cultural buildings in Semarang is effective in improving students' understanding of geometrical concept.